The Impact of Competitiveness, Information Technology, Risk Perception, and Financial Literacy on The Intention to Invest in Cryptocurrency - Satriya Miko; Aditya Wahyu Tri Atmaja; Risna Mawardah; Syifa Dwi Zulfa; Fernando Siboro; Arif Marjuki (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2023)
This study aims to analyze the impact of competence, information technology, risk perception, and financial literacy on interest in investing in cryptocurrency. The method used is quantitative, with data collected from 98 respondents through simple random sampling. The focus of this research is to reveal the relationship between factors that influence the interest of individuals who invest in cryptocurrencies. The results show that competency, information technology, risk perception, and financial literacy simultaneously or partially have a positive and significant effect on interest in cryptocurrency investment. These results suggest that the higher the competence of individuals in the field of financial knowledge and understanding of information technology, the greater their interest in investing in cryptocurrencies. In addition, the perception of low risk and high levels of financial literacy also contribute to increased interest in investing in cryptocurrencies. This research makes an important contribution in understanding the factors that influence the interest of individuals interested in cryptocurrencies. In the era of the rapidly developing digital economy, a deeper understanding of the impact of competency, information technology, risk perception and financial literacy has the potential to assist decision makers in developing more effective investment strategies and reducing risks. These findings also provide deeper insight into the dynamics of the cryptocurrency market and the consequences of growing investment in this sector. This research has actual relevance in the context of cryptocurrency investment, where the influence of factors such as competence, information technology, risk perception, and financial literacy on interest in investing is still not fully revealed. Through the help of the significant relationship between these factors and investment intentions, this research provides valuable insights for practitioners, academics, and decision makers to better understand and manage cryptocurrency investments more effectively. Thus, this research also makes an important contribution in developing knowledge and managing cryptocurrency investments in this increasingly digital era.